A non-aqueous electrolyte for lithium-ion battery and a lithium-ion battery
By using silicon-containing triflate sulfonate compounds and olefin-containing siloxane compounds as new additives in lithium-ion batteries, a high mechanical strength SEI film is solved, and the problem of instability of solid electrolyte interface film in lithium-ion batteries is significantly improved, and the battery cycle stability and high-temperature storage capacity retention rate are significantly improved.
Patent Information
- Application Number
- CN202311062154.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-23
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-08-23
AI Technical Summary
The solid electrolyte interface mask in lithium-ion batteries is unstable, resulting in low capacity retention and poor cycle life during long cycles.
Silicone-containing trifluoromethanesulfonate compound A and/or olefin-containing siloxane compound B are used as new additives, and combined with fluorovinyl carbonate, propylene sulfite and vinyl sulfate, a layer of uniform thickness and high mechanical strength SEI film is preferred on the negative electrode.
By forming a high mechanical strength SEI film, the volume expansion of the silicon carbon negative electrode is suppressed, the high-temperature storage capacity retention rate and cycle stability of the battery are improved, and the cycle life of the battery is extended.
Smart Images

Figure FDA0005235563990000011 
Figure FDA0005235563990000021 
Figure FDA0005235563990000022
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to a lithium ion battery non-aqueous electrolyte and a lithium ion battery. Background Art
[0002] In recent years, driven by both market and policy, the new energy industry has developed rapidly. As an important direction in the new energy field, lithium-ion batteries have obvious advantages over traditional secondary charging technologies, such as high energy density, long cycle life, and environmental protection. They have played an absolutely dominant role in the fields of power vehicles, energy storage, digital products, etc.
[0003] With the market demand for lithium-ion batteries with higher energy density and longer cycle life, using high specific capacity materials to replace traditional negative electrode materials is an effective means to improve battery energy density. 4.4 The theoretical specific capacity of Si is as high as 4200 mA·h·g -1 At the same time, it has suitable operating voltage, abundant reserves and good safety, and has great potential in battery negative electrode materials.
[0004] Pairing a high-nickel cathode with a silicon-carbon composite anode can provide a high-energy-density lithium-ion battery for automotive applications. The high-nickel cathode material generally selects a high-nickel layered oxide material with higher reversible capacity and lower cost, and the anode material selects a silicon-carbon composite material with high theoretical capacity and better structural stability, such as NCM811 batteries.
[0005] However, compared with graphite and lithium titanate as negative electrode materials, this type of battery has high oxidizability, and the volume of elemental silicon changes by up to 300% during charging and discharging. The large volume change can easily cause pulverization of electrode particles and shedding of active substances, resulting in poor battery cycle life.
[0006] The most commonly used method at present is to add additives to the electrolyte of lithium-ion batteries to form a solid electrolyte membrane, namely SEI membrane, on the surface of the electrode to stabilize the electrode surface and thus increase the cycle life of the electrode material.
[0007] Therefore, in the art, it is desired to develop an electrolyte that can solve the problems of instability of the solid electrolyte interface film in lithium-ion batteries and low capacity retention during long cycles. Summary of the invention
[0008] In view of the deficiencies of the prior art, an object of the present invention is to provide a lithium ion battery non-aqueous electrolyte and a lithium ion battery that are beneficial to improving the cycle performance of the battery.
[0009] One of the purposes of the present invention is to provide a non-aqueous electrolyte for lithium-ion batteries, the electrolyte comprising an electrolyte lithium salt, an organic solvent and a composite functional additive.
[0010] The composite functional additive comprises fluoroethylene carbonate, propylene sulfite, vinyl sulfate and a novel additive, wherein the novel additive comprises compound A as shown in formula 1 and / or compound B as shown in formula 2.
[0011]
[0012] wherein R1, R2, and R3 are each independently selected from an optionally substituted C1-C6 alkyl group or a trifluoromethanesulfonate group;
[0013] R4 is an optionally substituted C1-C6 alkyl group or an optionally substituted C1-C6 alkene group;
[0014] R5 and R6 are each independently selected from hydrogen, optionally substituted C1-C6 alkyl, optionally substituted C3-C9 cycloalkyl, optionally substituted C1-C6 alkene, optionally substituted C1-C6 alkoxy or optionally substituted C1-C6 alkenyloxy.
[0015] Preferably, based on the total mass of the electrolyte being 100%, the mass percentage of the novel additive is 0.5% to 7%.
[0016] Preferably, the novel additive comprises compound A and compound B.
[0017] Preferably, the mass ratio of compound A to compound B is 0.8-1.5:1.
[0018] Preferably, R1, R2, and R3 are each independently selected from any one of -CH3, -CH2CH3, -CH(CH3)2, -C(CH3)3, -CH2CH(CH3)2, -CH(CH3)2CH(CH3)2 or trifluoromethanesulfonate.
[0019] Preferably, R4 is selected from any one of -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -C(CH3)3 or -CH2CH2CH=CH2.
[0020] Preferably, R5 and R6 are each independently selected from any one of -CH3, -CH2CH3, -(CH2)3CH3, -(CH2)4CH3, -CH=CH2, -CH2CH=CH2, -(CH2)2CH=CH2, -OCH3 or -OCH2CH=CH2.
[0021] Preferably, the compound A comprises at least one of the compounds shown below;
[0022]
[0023] Preferably, the compound B comprises at least one of the compounds shown below;
[0024]
[0025]
[0026] Preferably, the electrolyte lithium salt includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate or lithium difluorobis(oxalatophosphate);
[0027] Preferably, the mass percentage of the electrolyte lithium salt is 10% to 50%.
[0028] Preferably, the organic solvent comprises one or more of carbonates, halogenated carbonates, carboxylates, propionates, fluoroethers, aromatic hydrocarbons or halogenated aromatic hydrocarbons;
[0029] Preferably, the mass percentage of the organic solvent in the electrolyte is 30% to 85%.
[0030] Preferably, the mass percentage of the composite functional additive is 1% to 15%.
[0031] Preferably, the mass ratio of fluoroethylene carbonate, propylene sulfite and vinyl sulfate is 4.5:2:1.
[0032] A second object of the present invention is to provide a lithium ion battery, wherein the lithium ion battery comprises the lithium ion battery non-aqueous electrolyte as described above.
[0033] The beneficial effects of the present invention include:
[0034] A silicon-containing trifluoromethanesulfonate compound A and / or an olefin-containing siloxane compound B are used as novel additives. Both compound A and compound B can preferentially form films with fluoroethylene carbonate, propylene sulfite and vinyl sulfate, forming a SEI film with uniform thickness and high mechanical strength on the silicon-carbon negative electrode to inhibit the volume expansion of the silicon-carbon negative electrode, improve the capacity retention rate of the battery after high-temperature storage and inhibit the high-temperature gas production of the battery, so that the SEI film has good thermodynamic stability and electrochemical stability. By adding, the electrode interface can be optimized, and the properties of the electrode / electrolyte interface film can be improved, forming a dense SEI film at the interface, reducing the impedance between the interfaces, inhibiting the dissolution of transition metals, and making the battery have excellent room temperature cycle stability and high temperature cycle stability. The capacity retention rate of the lithium ion battery using the electrolyte of the present invention can reach more than 76% after 1000 cycles at room temperature, and the capacity retention rate after 800 cycles at high temperature can reach more than 74%. DETAILED DESCRIPTION
[0035] In the following description, certain specific details are included to provide a comprehensive understanding of each disclosed embodiment. However, one skilled in the relevant art will recognize that the embodiments can be implemented without one or more of these specific details, but with other methods, components, materials, etc.
[0036] Unless otherwise required herein, the words "include" and "comprising" should be interpreted as having an open and inclusive meaning, ie, "including but not limited to."
[0037] References to "one embodiment" or "an embodiment" or "a preferred embodiment" or "certain embodiments" throughout this specification mean that the specific referenced elements, structures or features described in connection with the embodiment are included in at least one embodiment. Therefore, the phrases "in one embodiment" or "in an embodiment" or "in a preferred embodiment" or "in certain embodiments" appearing in different places throughout the specification do not necessarily all refer to the same embodiment. In addition, the specific elements, structures or features may be combined in any appropriate manner in one or more embodiments.
[0038] According to a first aspect of the present invention, a non-aqueous electrolyte for a lithium ion battery is provided, the electrolyte comprising an electrolyte lithium salt, an organic solvent and a composite functional additive.
[0039] The composite functional additive comprises fluoroethylene carbonate, propylene sulfite, vinyl sulfate and a novel additive, wherein the novel additive comprises compound A as shown in formula 1 and / or compound B as shown in formula 2.
[0040]
[0041] wherein R1, R2, and R3 are each independently selected from an optionally substituted C1-C6 alkyl group or a trifluoromethanesulfonate group;
[0042] R4 is an optionally substituted C1-C6 alkyl group or an optionally substituted C1-C6 alkene group;
[0043] R5 and R6 are each independently selected from hydrogen, optionally substituted C1-C6 alkyl, optionally substituted C3-C9 cycloalkyl, optionally substituted C1-C6 alkene, optionally substituted C1-C6 alkoxy or optionally substituted C1-C6 alkenyloxy.
[0044] In the present invention, a silicon-based trifluoromethanesulfonate compound A is used as a novel additive, and -CF3 is an electron-withdrawing group, so that the compound A molecule has a lower lowest unoccupied orbital (LUMO) energy level and a higher reduction potential, and can be preferentially decomposed, and preferentially form a film with fluoroethylene carbonate, propylene sulfite and vinyl sulfate at the negative electrode, and form a SEI film with uniform thickness and high mechanical strength at the silicon-carbon negative electrode to inhibit the volume expansion of the silicon-carbon negative electrode, improve the capacity retention rate of the battery after high-temperature storage, and inhibit the high-temperature gas production of the battery. The Si-O structure in compound A is introduced into the SEI film, which can make the SEI film have good thermodynamic stability and electrochemical stability. Due to the large number of valence states of S, the decomposition mechanism under the action of the electrolyte group and the external voltage, the formed SEI film has excellent mechanical properties and stability, and at the same time, it is also beneficial to reduce the polarization of the battery.
[0045] In addition, compound A can make the SEI film contain more inorganic LiF components. On the one hand, the accumulation of LiF makes the SEI film structure more compact, which is more conducive to preventing the electrolyte from passing through the SEI film and improving the mechanical strength and stability of the film; on the other hand, it provides a fast Li + The LiF-rich SEI film alleviates the volume expansion during the cycle and stabilizes the electrode structure.
[0046] In the present invention, on the one hand, the silicon oxygen group in compound B can effectively control the water acid content in the electrolyte; on the other hand, the Si-O structure and carbon-carbon double bond in compound B, as a new additive, preferentially form a film with fluoroethylene carbonate, propylene sulfite and vinyl sulfate at the negative electrode, and can form a denser SEI film with a cross-linked network structure, so that the mechanical strength of the SEI film is more stable, thereby inhibiting the volume expansion of the silicon-carbon negative electrode.
[0047] In a preferred embodiment of the present invention, based on the total mass of the electrolyte being 100%, the mass percentage of the novel additive is 0.5% to 7%.
[0048] In the present invention, when the mass percentage of the novel additive is less than 0.5%, the mechanical properties and stability of the SEI film are poor, and it is easy to be destroyed during the use of the battery, resulting in poor cycle stability; when the mass percentage of the novel additive is greater than 7%, during the formation of the SEI film, according to the mosaic model, the outer organic film is formed too quickly, so that the inner inorganic stacking layer structure is loose, which will affect the mechanical strength of the SEI film on the one hand, and weaken the ability of the SEI film to block the electrolyte on the other hand. Therefore, the mass percentage of the novel additive is 0.5% to 7%, for example, 0.5%, 0.7%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 4%, 5%, 6% or 7%.
[0049] In a preferred embodiment of the present invention, the novel additive comprises compound A and compound B.
[0050] In the present invention, compound A and compound B react synergistically with fluoroethylene carbonate, propylene sulfite and vinyl sulfate to form a denser SEI film with a cross-linked network structure, making the mechanical strength of the SEI film more stable.
[0051] Preferably, the mass ratio of compound A to compound B is 0.8-1.5:1.
[0052] In the present invention, the mass ratio of compound A to compound B is, for example, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1 or 1.5:1.
[0053] In a preferred embodiment of the present invention, R1, R2, and R3 are each independently selected from any one of -CH3, -CH2CH3, -CH(CH3)2, -C(CH3)3, -CH2CH(CH3)2, -CH(CH3)2CH(CH3)2 or trifluoromethanesulfonate.
[0054] In a preferred embodiment of the present invention, R4 is selected from any one of -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -C(CH3)3 or -CH2CH2CH=CH2.
[0055] Preferably, R5 and R6 are each independently selected from any one of -CH3, -CH2CH3, -(CH2)3CH3, -(CH2)4CH3, -CH=CH2, -CH2CH=CH2, -(CH2)2CH=CH2, -OCH3 or -OCH2CH=CH2.
[0056] In a preferred embodiment of the present invention, the compound A comprises at least one of the compounds shown below;
[0057]
[0058]
[0059] In a preferred embodiment of the present invention, the compound B comprises at least one of the compounds shown below;
[0060]
[0061]
[0062] In a preferred embodiment of the present invention, the electrolyte lithium salt includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate or lithium difluorobis(oxalatophosphate).
[0063] In the present invention, the electrolyte lithium salt is, for example, lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate, lithium difluorobis(oxalatophosphate), lithium hexafluorophosphate and lithium bis(trifluoromethylsulfonyl)imide, lithium hexafluorophosphate and lithium bis(fluorosulfonyl)imide, or a combination of lithium hexafluorophosphate, lithium tetrafluoroborate and lithium bis(fluorosulfonyl)imide.
[0064] Preferably, the mass percentage of the electrolyte lithium salt is 10% to 50%.
[0065] In the present invention, the electrolyte lithium salt is, for example, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45% or 50%.
[0066] In a preferred embodiment of the present invention, the organic solvent comprises one or more of carbonates, halogenated carbonates, carboxylates, propionates, fluoroethers, aromatic hydrocarbons or halogenated aromatic hydrocarbons.
[0067] Preferably, the carbonate includes one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate or ethyl methyl carbonate.
[0068] Preferably, the halogenated carbonate includes at least one or more of fluoroethylene carbonate, difluoroethylene carbonate, difluoropropylene carbonate, trifluoroethyl acetate, trifluoroethyl methyl carbonate, trifluoromethylethylene carbonate, 4-trifluoromethylethylene carbonate, chloroethylene carbonate, di(2,2,2-trifluoroethyl) carbonate, methyl trifluoropropionate, 3,3,3-trifluoroethyl acetate, methyl 2-(trifluoromethyl)benzoate, ethyl 4,4,4-trifluorobutyrate or 1,1,1,3,3,3-hexafluoroisopropyl acrylate.
[0069] Preferably, the carboxylic acid ester includes one or more of propyl butyrate, propyl acetate, isopropyl acetate, butyl propionate, isopropyl propionate, ethyl butyrate, methyl propionate, ethyl propionate or propyl propionate.
[0070] Preferably, the propionate ester includes one or more of methyl propionate, ethyl propionate or propyl propionate.
[0071] Preferably, the fluoroether comprises one or more of C2 to C7 fluorine-substituted ethers.
[0072] Preferably, the halogenated aromatic hydrocarbon is one or more of monofluorobenzene, difluorobenzene, 1,3,5-trifluorobenzene, trifluorotoluene, 2-fluorotoluene or 2,4-dichlorotrifluorotoluene.
[0073] Preferably, the mass percentage of the organic solvent in the electrolyte is 30% to 85%.
[0074] In the present invention, the mass percentage of the organic solvent is, for example, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%.
[0075] Preferably, the organic solvent includes ethylene carbonate, ethyl methyl carbonate and diethyl carbonate.
[0076] Preferably, the mass ratio of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate is 25:70:5.
[0077] Preferably, the mass percentage of the composite functional additive is 1% to 15%.
[0078] In the present invention, the mass fraction of the composite functional additive is, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%.
[0079] Preferably, the mass ratio of fluoroethylene carbonate, propylene sulfite and vinyl sulfate is 4.5:2:1.
[0080] According to a second aspect of the present invention, a lithium ion battery is provided, wherein the lithium ion battery comprises the lithium ion battery non-aqueous electrolyte as described above.
[0081] Preferably, the positive electrode material of the lithium-ion battery is a ternary positive electrode material of nickel-cobalt-lithium manganese oxide.
[0082] Preferably, the negative electrode material of the lithium-ion battery is a silicon-carbon composite material.
[0083] Example
[0084] The present invention is further described in detail below in conjunction with the embodiments. It is to be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other.
[0085] In the following examples, unless otherwise specified, all raw materials are commercially available products.
[0086] First, the preparation steps of the electrolyte include:
[0087] (1) Remove water from organic solvents and composite functional additives to control the water content to <15ppm;
[0088] (2) Adding the composite functional additive and electrolyte lithium salt into an organic solvent and stirring to dissolve them to obtain an electrolyte solution.
[0089] Example 1 uses compound A as shown in formula 1-2 and compound B as shown in formula 2-1;
[0090]
[0091] Example 2 uses compound A as shown in formula 1-2 and compound B as shown in formula 2-6;
[0092]
[0093] Example 3 uses compound A as shown in formula 1-2 and compound B as shown in formula 2-9;
[0094]
[0095] Example 4, Example 18, Example 19, Example 20 and Example 23 use compound A as shown in formula 1-2 and compound B as shown in formula 2-10;
[0096]
[0097] Example 5 uses compound A as shown in formula 1-4 and compound B as shown in formula 2-2;
[0098]
[0099] Example 6 uses compound A as shown in formula 1-4 and compound B as shown in formula 2-3;
[0100]
[0101] Example 7 uses compound A as shown in formula 1-4 and compound B as shown in formula 2-7;
[0102]
[0103] Example 8 uses compound A as shown in formula 1-4 and compound B as shown in formula 2-9;
[0104]
[0105] Example 9 uses compound A as shown in formula 1-6 and compound B as shown in formula 2-4;
[0106]
[0107] Example 10 uses compound A as shown in formula 1-6 and compound B as shown in formula 2-8;
[0108]
[0109] Example 11 uses compound A as shown in formula 1-6 and compound B as shown in formula 2-11;
[0110]
[0111] Example 12 uses compound A as shown in formula 1-6 and compound B as shown in formula 2-10;
[0112]
[0113] In Example 13, Example 16 and Example 17, Compound A as shown in Formula 1-2 is used, and Compound B is not used;
[0114]
[0115] Example 14 uses compound A as shown in formula 1-4, and does not use compound B;
[0116]
[0117] Example 15 uses compound A as shown in formula 1-6, and does not use compound B;
[0118]
[0119] Example 21 uses compound B as shown in formula 2-9, and does not use compound A;
[0120]
[0121] Example 22 uses compound B as shown in formula 2-11, and does not use compound A;
[0122]
[0123] Comparative Example 1 does not use compound A and compound B;
[0124] Taking the total mass of the lithium ion battery non-aqueous electrolyte as 100%, the electrolyte compositions of Examples 1-22 and Comparative Example 1 are shown in Table 1:
[0125] Table 1 Electrolyte compositions of Examples 1-22 and Comparative Example 1
[0126]
[0127]
[0128]
[0129] The electrolytes of Examples 1 to 22 and Comparative Example 1 were added to a battery to prepare a lithium ion battery:
[0130] The positive electrode uses a binder PVDF-900, a composite conductive agent Super-P, a nickel cobalt manganese oxide (NCM811) ternary positive electrode material, and a solvent NMP (N-methyl-2-pyrrolidone).
[0131] The negative electrode uses silicon-carbon composite material (model: BYD S420-A), conductive agent Super-P, solvent CMC, H2O, and binder SBR as raw materials. The lithium-ion soft-pack battery is prepared by coating, slicing, rolling, slitting, drying, taping, winding the battery cell, and drying at 80°C for 48 hours. Then, the lithium-ion battery is filled and sealed according to the following different electrolyte formulas, left for 24 hours, formed, first sealed, aged, and second sealed.
[0132] Then the battery is tested for high temperature cycle performance and high temperature storage performance:
[0133] Cycle performance: The charge and discharge voltage range is 2.75V to 4.20V, the charging current is 1C (2.0A) to 4.20V, 4.20V constant voltage charging to the cut-off current ≤ 0.05C (0.1A), after standing for 5 minutes, 1C (2.0A) discharge to 2.75V, stand for 5 minutes; cycle discharge and calculate the capacity retention rate of different cycles. The test results are shown in Table 2 and Table 3:
[0134] Table 2 25℃ room temperature cycle capacity retention rate
[0135]
[0136]
[0137] Table 3 Battery 45℃ high temperature cycle capacity retention rate
[0138]
[0139]
Claims
1. A non-aqueous electrolyte for lithium-ion batteries, characterized in that: The electrolyte comprises electrolyte lithium salt, organic solvent and composite functional additive; The composite functional additive includes fluoroethylene carbonate, propylene sulfite, vinyl sulfate and a novel additive, wherein the novel additive includes a combination of compound A as shown in formula 1 and compound B as shown in formula 2, or compound B as shown in formula 2; wherein R1, R2, and R3 are each independently selected from an optionally substituted C1-C6 alkyl group or a trifluoromethanesulfonate group; R4 is an optionally substituted C1-C6 alkyl group or an optionally substituted C1-C6 alkene group; R5 and R6 are each independently selected from hydrogen, optionally substituted C1-C6 alkyl, optionally substituted C3-C9 cycloalkyl, optionally substituted C1-C6 olefin, optionally substituted C1-C6 alkoxy or optionally substituted C1-C6 alkenyloxy; The total mass of the electrolyte is 100%, and the mass percentage of the composite functional additive is 1% to 15%; The mass percentage of the novel additive is 0.5% to 7%; When the novel additive is compound A and compound B, the mass ratio of compound A to compound B is 0.8 to 1.5:1; The mass ratio of fluoroethylene carbonate, propylene sulfite and vinyl sulfate is 4.5:2:
1.
2. The non-aqueous electrolyte for lithium-ion batteries according to claim 1, characterized in that: R1, R2, and R3 are each independently selected from any one of -CH3, -CH2CH3, -CH(CH3)2, -C(CH3)3, -CH2CH(CH3)2, -CH(CH3)2CH(CH3)2 or trifluoromethanesulfonate.
3. The non-aqueous electrolyte for lithium-ion batteries according to claim 1, characterized in that: R4 is selected from any one of -CH3, -CH2CH3, -CH2CH2CH3, -CH(CH3)2, -C(CH3)3 or -CH2CH2CH=CH2; R5 and R6 are each independently selected from any one of -CH3, -CH2CH3, -(CH2)3CH3, -(CH2)4CH3, -CH=CH2, -CH2CH=CH2, -(CH2)2CH=CH2, -OCH3 or -OCH2CH=CH2.
4. The non-aqueous electrolyte for lithium ion batteries according to claim 1, characterized in that: The compound A comprises at least one of the compounds shown below; 5. The non-aqueous electrolyte for lithium ion batteries according to claim 1, characterized in that: The compound B includes at least one of the compounds shown below; 6. The non-aqueous electrolyte for lithium-ion batteries according to claim 1, characterized in that: The electrolyte lithium salt includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorophosphate or lithium difluorobis(oxalatophosphate); The mass percentage of the electrolyte lithium salt is 10% to 50%.
7. The non-aqueous electrolyte for lithium-ion batteries according to claim 1, characterized in that: The organic solvent includes one or more of carbonate, halogenated carbonate, carboxylate, propionate, fluoroether, aromatic hydrocarbon or halogenated aromatic hydrocarbon; The mass percentage of the organic solvent in the electrolyte is 30% to 85%.
8. A lithium ion battery, characterized in that: The lithium ion battery comprises the lithium ion battery non-aqueous electrolyte according to any one of claims 1 to 7.
Citation Information
Patent Citations
High-voltage electrolyte and lithium ion battery
CN114497741A
Low-impedance water removal electrolyte additive for lithium ion battery, non-aqueous electrolyte, lithium ion battery and electric equipment
CN116154290A